SILVER NANOPARTICLES AND COCONUT OIL INCORPORATED BIOPOLYMER BASED ELECTROSPUN NANOFIBERS FOR WOUND DRESSING - SAHOO, SUBHASHREE; TRIPATHY, JOGABRATA; MOIN, AFRASIM; S., MEENAKSHI; SIDDARAMAIAH; GOWDA, D.V. (International Journal of Applied Pharmaceutics, 2021)
Objective: The main aim of this study was to develop and evaluate the nanofiber loaded with coconut oil and silver nanoparticles (Ag NPs) for the treatment of wound healing by the electrospun method. Methods: The nanofibers have been created using the reduced form of silver nanoparticles and coconut oil along with Eudragit L-100 by the electrospun method. The presence of coconut oil and chemical interaction was determined by the FTIR method. XRD was made to evaluate the crystalline nature of AgNPs and Eudragit L-100. TEM was carried out to show the presence of AgNPs on the surface of nanofibers and SEM represents the diameter of the fiber. The antibacterial activity of nanofibers was carried out using a disk diffusion assay. Results: The diameter of the fibers was diminished by the excess of AgNPs in the fibers, while it increases by the coconut oil concentration, enhancing the nanofiber's hydrophilicity. FTIR spectroscopy was found in the range of coconut oil at 3553 cm-1for O-H stretch, 1365 cm-1, and 1240 cm-1 for the C-O stretch of ester groups. The diffraction peaks at 2θ of 38.5°, 44.6°, and 64.7°, in the XRD spectra of nanofiber, changed with silver NP affirming the total decrease of Ag salt. The bactericidal activity has been carried out between Escherichia coli and Staphylococcus aureus showing zones of inhibition of 20.0±0.2 mm and 14.8±0.4 mm, exhibiting excellent bactericidal characteristics for wound healing. Conclusion: The formulated nanofibers were obtained to offer protection against external agents and help in the regeneration of new tissue.